KAJIAN PEMBENTUKAN KARBON AKTIF BERBAHAN ARANG TEMPURUNG KELAPA - Esmar Budi; Hadi Nasbey; Setia Budi; Erfan Handoko; Puji Suharmanto; Ranggi Sinansari; Sunaryo Sunaryo (PROSIDING SEMINAR NASIONAL FISIKA (E-JOURNAL), 2012)
The early study on preparation, process and characterization of activated carbon from coconut shell charcoal has being done to achieve the optimum activated carbon performance. The preparation involved cleaning, drying and sequent sieving and heat treatment. The coconut shell was pyrolyzed at temperature about 70 – 1000C for about 6 hours. The coconut shell charcoal then was sieved once to produce rough powder while finer powder was achieved by twice sieving. SEM analysis result showed that the coconut shell charcoal morphology has pore structure in about micro size. From EDS analysis, the major element content of charcoal was carbon C (82.92 %wt). From PSA analysis, it showed that differential volume of rough charcoal powder was distributed into 5.610 – 6.760 µm (41.14 %) and 15.65 – 17.18 µm (32.83%) while finer charcoal powder was distributed into 0.452 – 3.519 µm (99,77%). Keywords: Coconut shell charcoal, pyrolysis, activated carbon, pore.